(untitled) (Medico Legal Update, 2021)
Case control study was carried out in Salah-Addin city in private ophthalmology clinic from 1st November of 2019 to End february 2020. The study included 90 individuals including sixty diabetic patients (30 who had retinopathy and 30 without retinopathy) and 30 healthy individuals to evaluate the level of Malondialdehyde (MDA) in diabetic patients with and without retinopathy and healthy controls. All patients were aged between (51-82) years, with a negative history of antioxidant supplementation consumption. Blood samples were collected from each patients and controls to evaluate the levels of malondialdehyde and HbA1c by using immunofluorescence technique. The study showed that majority of diabetic retinopathy (DR) patients were females and the highest mean of age was recorded in diabetic retinopathy patients (60.76±7.25 year) compared with diabetic without retinopathy patients (58.31±9.19 year). The study displayed that the highest mean of MDA was recorded in DR patients as compared with diabetic without retinopathy patients (390.37±108.68 vs 336.97±94.95 ng/ml), although the result was non-significant (P: > 0.05). The study showed that the highest mean of MDA was in DR patients (390.37±108.68 ng/ml) followed by diabetic without retinopathy patients (336.97±94.95 ng/ml) and the lowest mean was in healthy individuals (293.32±42.51 ng/ml), (P: < 0.05). The study showed that, HbA1c was elevated significantly (P<0.05) in diabetic retinopathy patients (9.26±1.54) compared with diabetic without retinopathy patients (7.84±1.02). The present study displayed that the highest mean of duration of DM was recorded in diabetic retinopathy patients (13.48±6.00) compared with Diabetic without retinopathy patients (6.34±2.78), the result was significant (P:<0.05). The study showed negative correlation between HbA1c and BMI in DR patients; and no correlation between HbA1c and BMI in DM patients without retinopathy, The study showed negative correlation between MDA and HbA1c in DR patients and no correlation in DM patients without retinopathy. Conclusion: Long duration of DM and the old age were risk factors for DR, poor control of was more disposed to develop retinopathy and oxidative stress is still higher in diabetic patients with retinopathy than patients without retinopathy.